Hepatitis E virus and blood transfusion safety. (29th June 2020) - Bi, Hao; Yang, Ru; Wu, Chunchen; Xia, Jianbo
Abstract: While the majority of worldwide hepatitis E viral (HEV) infections that occur in people are from contaminated water or food sources, there has also been a steadily rising number of reported cases of transfusion-transmitted HEV (TT-HEV) in blood donation recipients. For most, HEV infection is acute, self-limiting and asymptomatic. However, patients that are immunocompromised, especially transplant patients, are at much higher risk for developing chronic infections, which can progress to cirrhosis and liver failure, along with overall increased mortality. Because of the rising trend of HEV serological prevalence among the global population, and the fact that TT-HEV infection can cause serious clinical consequences among those patients most at need for blood donation, the need for screening for TT-HEV has been gaining in prominence as an important public health concern for both developing and developed countries. In the review, we summarise evidence for and notable cases of TT-HEV infections, the various aspects of HEV screening protocols and recent trends in the implementation of TT-HEV broad-based blood screening programmes.